Content analysis and engagement rate of instagram account @torajatripadventure and interest in visiting tourists to Tana Toraja tourism destinations - Farid Asfari Rahman; Mas Dadang Enjat Munajat; Evi Novianti (Universitas Merdeka Malang, 2022)
Tana Toraja Regency is one of the districts located in South Sulawesi. Natural beauty, cultural diversity, and customs that are still very thick become one of the characteristics that are not found in other regions. This study aims to 1). identify the content of the Instagram account @torajatripadventure, 2). identify the engagement rate of the Instagram account @torajatripadventure, and 3). identify interest in visiting Tana Toraja Regency. This research uses a quantitative descriptive research design. This study was conducted by sending an online questionnaire via google form to Instagram account followers @torajatripadventure which is known to number 52,600. The sample in this study was 100 people who became followers of the Instagram account @torajatripadventure and the category was determined based on random sampling. Data collection is obtained through questionnaires. The results of this study indicate that 1). Product content and event content are considered interesting, useful, and informative. Furthermore, entertainment content is considered attractive and entertaining even though it is still not useful and promotional content is considered attractive but not useful and persuasive. 2). The four contents are included in the low level of interaction category because the engagement rate is below 1%, however, event content is still the content with the highest engagement rate, followed by entertainment content, product content and promotional content. 3). The dimension of interest and the dimension of desire are the dimensions that most interest respondents, followed by the dimension of seeking information, the dimension of consideration and the dimension of action. As for the average value for calculating the type of content on interest in visiting, event content is the content that gets the highest response from respondents, followed by product content, entertainment content and promotional content.